The Association Between Lymph Node Stage and Clinical Prognosis in Thyroid Cancer - Zhang, Junyi; Cheng, Xiaoyun; Shen, Lei; Wang, Xingchun; Wang, Lu; Sun, Xiaoting; Qu, Shen (Frontiers in Endocrinology, 2020)
Purpose: To investigate the association between lymph node (N) stage and clinical outcome in thyroid cancer patients with initial distant metastasis. Methods: A total of 3,198 cases (1,435 males and 1763 females) between 2004 and 2015 with initial distant metastasis were obtained from the surveillance, epidemiology, and end results (SEER) database. Patients with a median follow up time of 13 months and a median age of 66 years were analyzed. A total of 1,407 cases had detailed information regarding the four most common metastatic organs after the year 2010. Kaplan-Meier (KM) analyses, log-rank tests, Cox regression, and logistic regression analyses were used. Results: Among the whole cohort, 33.4% (1,069/3,198), 14.5% (464/3,198), 10.1% (322/3,198), 34.2% (1,094/3,198), and 7.8% (249/3,198) of the patients were at the stage of N0, NX, N1a, N1b, and N1NOS, respectively. The KM curves demonstrated that the patients at the NX stage had the worst survival. The NX and N1b groups had the highest hazard ratios (HRs) of 1.83 (95%CI 1.46-2.31) and 1.78 (95%CI 1.52-2.10) after adjusting age, race, gender, and tumor size (p<0.001) compared with N0 group. The lung was the most common metastatic site, with a rate of 51.2% (720/1,407). Compared with the N0 group, N1 patients had higher odds (OR 1.63, 95%CI 1.31-2.01, p<0.001) for lung metastasis. Similar results were obtained in papillary thyroid cancer sub-cohort. Conclusions: Overall, the TC patients at the NX stage had the highest mortality risk, followed by N1b, N1a, and N0 groups. Compared with N0 patients, N1 patients were more likely to have lung metastasis. The poor prognosis for TC patients with the NX stage may make more aggressive treatment reasonable.